Detailed numerical simulation of cathode spots in vacuum arcs—I - Cunha, Mário D. (2022)
A model of cathode spots in high-current vacuum arcs is developed, with account of the plasma cloud left over from a previously existing spot, all mechanisms of current transfer to the cathode surface, including the contribution of the plasma produced by ionization of the metal vapor emitted in the spot, and the Joule heat generation in the cathode body. The simulation results allow one to clearly identify the different phases of life of an individual spot: the ignition, the expansion over the cathode surface, and the thermal explosion. The expansion phase is associated with a nearly constant maximum temperature of the cathode, which occurs at the surface and is approximately 4700–4800 K. Thermal explosion is a result of thermal instabil ity (runaway), which develops below the cathode surface when the Joule heating comes into play. The development of the spot is interrupted if the plasma cloud has been extinguished: the spot is destroyed by heat removal into the bulk of the cathode due to thermal conduction. Therefore, different scenarios are possible depending on the time of action of the cloud: the spot may be quenched before having been formed or during the expansion phase, or even at the initial stage of thermal explosion.